A single-center, cross-sectional study of cross-professional faculties' perception to virtual class under different scenarios: A stepwise approach. Issue 7 (30th June 2022) - Lin, Yu-Fan; Chen, Chen-Huan; Yang, Ying-Ying; Kuo, Nai-Rong; Li, Tzu-Hao; Lirng, Jiing-Feng; Hou, Ming-Chih; Huey-Herng Sheu, Wayne
Abstract : Background: Virtual teaching in medical education is rising with the increased need caused by the recent pandemic. However, evaluations of the perception of clinical teachers across professions for setting a virtual class in different teaching scenarios are limited. This study aims to identify cross-professional clinical teachers' perception of virtual classes and the acceptability of the virtual class-specific checklist for setting a virtual class. Methods: We conducted a cross-sectional study to investigate clinical teachers' need to set and teach a virtual class and then designed a virtual class-specific checklist with five essential steps and a related training program in July 2021. After the training, 186 participants were randomly enrolled in October 2021 to evaluate their perceptions about setting virtual classes and the acceptability of the virtual class-specific checklist using an online assessment questionnaire. Results: In our institution, the number of faculty-led virtual classes has recently been on the increase. Our study revealed that most teachers agreed that virtual classes could break space and time limitations, but that the Internet environment could affect the fluency of the virtual class. They further agreed that the essential five steps in the checklist should vary depending on the type of teaching scenario. Most clinical teachers, with the exception of those who teach in the operating room, considered the operating room as the most difficult scenario for setting virtual classes. Conclusion: Faculty training for setting virtual classes is essential, and the essential virtual class-specific five steps are suitable for different teachers and teaching scenarios. However, the virtual class-specific checklist should be further adjusted according to the limitations caused by emerging innovative virtual teaching technology.